Epstein–Barr virus infection plays a crucial role in triggering hemophagocytic lymphohistiocytosis in patients with X-linked inhibitor of apoptosis protein deficiency - Lin Shi; Liurui Dou; Jingshi Wang; Zhao Wang (Hematology)
Background X-linked inhibitor of apoptosis protein (XIAP) deficiency is a congenital immunodeficiency disorder characterized by increased susceptibility to Epstein–Barr virus (EBV) infection and is frequently associated with hemophagocytic lymphohistiocytosis (HLH).Objective To investigate the correlation between EBV and XIAP deficiency-related HLH, including EBV infection status, XIAP genetic mutation sites, and the efficacy of different treatment regimens in patients with EBV-positive XIAP deficiency-related HLH, and to analyse the prognosis of these patients.Methods We retrospectively analysed patients diagnosed with EBV-positive XIAP deficiency-related HLH.Results Data were collected from August 2017 to August 2024, and 10 patients were included in this study. All patients exhibited an elevated EBV-DNA load. EBV-DNA was detected in both plasma (2/10) and peripheral blood mononuclear cells (10/10), specifically B cells (9/9) and T cells (4/9). Treatment regimens containing rituximab, HLH-2004, and dexamethasone with or without ruxolitinib achieved complete remission. However, only the regimen containing rituximab successfully eradicated EBV from plasma and peripheral blood mononuclear cells in all patients. None of the patients underwent allogeneic haematopoietic stem cell transplantation. No cases of HLH recurrence or EBV reactivation were observed during a median follow-up of 28 months.Conclusions EBV infection plays a crucial role in triggering HLH in patients with XIAP deficiency. XIAP deficiency-related HLH is frequently associated with EBV infection, which predominantly affects B cells. Treatment regimens containing rituximab can effectively control HLH and eliminate EBV infection. Allogeneic haematopoietic stem cell transplantation may be avoidable in paediatric patients achieving EBV eradication through rituximab-containing regimens.